Pengaruh Variasi Beban terhadap Faktor Kekuatan Rangka Sepeda dari Bahan AISI 1035 Steel (SS) dengan Simulasi Solidworks - Muhlisin, Iip; Sudiman, Sudiman (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to investigate the impact of load variations in the range of 140 Kgf to 240 Kgf on the strength factor of bicycle frames made of metal material, namely AISI 1035 Steel (SS), through Solidworks simulations. The parameters used in the simulation evaluation are the load or force that occurs, stress or von Mises, displacement and factor of safety. The main focus of the research is to evaluate the structural response of the bicycle frame to these load variations and identify the most optimal loading, taking into account a safety factor of 2.5 applied to the design. The Solidworks simulation method is used to analyze the maximum stress that occurs (114.3 N/mm2) and maximum displacement (0.245 mm) in the bicycle frame. This simulation includes the application of gradual loads to a bicycle frame model, and stress and displacement calculations are carried out in detail. The results show that the most ideal loading occurs below 220 Kgf, indicating optimal structural stability and safety. The conclusions from these findings provide deep insight into the performance of bicycle frames in the face of certain load variations. Potential implications include the development of more efficient and safer bicycle frame designs, contributing to increased safety and comfort for bicycle users.